α‐Glucosidase inhibitory and antioxidant activities of different ipomoea aquatica cultivars and LC–MS/MS profiling of the active cultivar - Lawal, Umar; Leong, Sze Wei; Saari, Khozirah; Ismail, Intan Safinar; Khatib, Alfi; Abas, Faridah (Wiley Periodicals, Inc., 2017)
The present study was designed to investigate the effect of Ipomoea aquatica extracted using water and methanol at various concentrations on the total phenolics, antioxidant capacity, and a-glucosidase inhibitory activities. Three I. aquatica cultivars were used in this study including the upland type with narrow leaves (K-11), low-land aquatic types with broader shaped leaves (K-25), and bamboo-shaped leaves (K-88). The results revealed that 70% methanol extract of K-11 showed higher total phenolic content and a-glucosidase inhibitory and antioxidant activities than the other two cultivars. The phytochemical constituents in the active extract K-11 were analyzed by means of liquid chromatography coupled with diode array detection and electrospray tandem mass spectroscopy. Eighteen compounds were detected of which 13 were tentatively identified as quercetin-3-O-sophoroside, quercetin-3-O-glucoside, quercetin-3,7-di-O-glucoside, nomilinic acid glucoside, 4,5-di-O-caffeoylquinic acid, 3,5-di-O-caffeoylquinic acid, luteolin-7-glucoside and 3,4,5-tricaffeolquinic acid, fatty acid together with quercetin, and tricaffeoylquinic acid derivatives.